Rancangan Sistem Perencanaan Produksi dan Pengendalian Persediaan dengan Mempertimbangkan Efisiensi Biaya Pada PT. X - Yunita Velany Sulayman; Herry Christian Palit (Jurnal Titra, 2013)
PT. X is a manufacturing company with produce crude oil and cooking oil. The company has problem with determination appropriate of ROP which caused stock out in some products that produced by PT. X. Analyze of stock out condition did while 2011 and 2012. PT. X apply make to stock system. Metode that used at this project is continuous review policy to determine the appropriate of ROP and minimize the cost which adjusted with PT. X condition. The results of improvement of opportunity is there are different ROP and maximum capacity. The improvement will analyzed of the cost and compared with actual system. Cost reduce that resulted are 22% for first improvement and 15% for second improvement. Company can consider both of improvement with their profit.